2012
DOI: 10.1080/09603107.2012.654912
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure adjustments in private business group companies

Abstract: The literature on capital structure dynamics assumes that companies tradeoff the advantages of a leverage adjustment and its costs. In general, private companies are assumed to face relatively large adjustment costs, and should have lower financing flexibility. However, we argue that an important class of private companies -business group affiliates -may face relatively low adjustment costs because of their access to both internal and external capital markets and the beneficial reputation effects of belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Kim, Heshmati, and Aoun (2006) studied the Korean firms to examine the same and found that group firms in Korea adjust their capital structure faster than the stand-alone firms. Similar results were documented by Dewaelheyns and Hulle (2012) for the Belgian firms. On the contrary, Ghose (2017) examined the Indian firms and found slower adjustment speed for group firms than their stand-alone counterparts.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Kim, Heshmati, and Aoun (2006) studied the Korean firms to examine the same and found that group firms in Korea adjust their capital structure faster than the stand-alone firms. Similar results were documented by Dewaelheyns and Hulle (2012) for the Belgian firms. On the contrary, Ghose (2017) examined the Indian firms and found slower adjustment speed for group firms than their stand-alone counterparts.…”
Section: Introductionsupporting
confidence: 87%
“…This confirms the hypothesis that there is asymmetry in adjustment speed between the group and stand-alone firms. The lower adjustment speed for group firms is against the findings of Kim et al (2006) and Dewaelheyns and Hulle (2012) for Korean and Belgian firms, respectively. Two possible explanations emerge from this result.…”
Section: Resultsmentioning
confidence: 57%
“…We use a two‐stage estimation procedure, which is analogous to the debt/equity choice test methodology of Hovakimian, Opler, and Titman (), but adjusted for private firms (cf., Dewaelheyns and Van Hulle ). In a first stage we estimate the target leverage ratio, Leverage* , which is the debt ratio a firm would choose in absence of transaction costs, adjustment costs, and information asymmetries.…”
Section: Methodology and Variablesmentioning
confidence: 99%
“…This inverse relationship should especially hold true in our SME setting, as the external financing options of small firms are more limited (Chittenden, Hall, and Hutchinson ; Psillaki and Daskalakis ; Titman and Wessels ). Profitability is defined as net earnings over total assets (Dewaelheyns and Van Hulle ). Further, a change in the growth opportunities of a firm ( ΔGrowth ) is likely to affect the need for extra external financing and hence the likelihood of a change in leverage level (Hovakimian, Opler, and Titman ).…”
Section: Methodology and Variablesmentioning
confidence: 99%
“…Characteristics of the sampleThe industry classification was based on the NACE Rev. 2's main section and is according to the aggregation ofFama and French's (1997) industry classification presented byDewaelheyns and Van Hulle (2012).…”
mentioning
confidence: 99%